The Relevance of the Qur'an to Piaget's Stages of Cognitive Development: A Critical Analysis and Perspective on Childhood Education: Relevansi Al-Qur’an terhadap Tahapan Perkembangan Kognitif Piaget: Analisis Kritik dan Perspektif Pendidikan Anak - Ika Wahyuningsih; Sumedi (STAI Terpadu Yogyakarta, 2025)
Piaget's cognitive theory has been used extensively in modern education, but it is not entirely free from criticism. The values of the Qur'an present a more holistic cognitive approach rooted in the value of spirituality. This study aims to reveal the relevance of the Qur'anic values in the context of Piaget's theory of cognitive development, so as to provide a more contextual guide to the needs of children's intellectual development. The type of research is qualitative descriptive with a literature study approach. Data collection is carried out by tracing data sources, including books, articles, news, and other related documents. The data analysis technique uses content analysis. The results of the study show that the Qur'an is relevant to the four stages of Piaget's cognitive theory, namely sensorimotor, pre-operational, concrete operational, and formal operational, reviewed from the rules and recommendations that must be carried out when a child passes through certain phases. The Qur'an contextually pays attention to the psychological development of children. The Qur'an has a theory that answers reality better, when Piaget's theory received criticism about the difference in children's cognitive abilities at the same age or phase, as evidenced by the discovery that concluded that there is a difference in children's cognitive level after 6-12 years. Based on the perspective of Qur'anic values, cognitive development does not have to be spurred by measuring the age of children specifically as formulated by Piaget's cognitive theory.